The importance and efficiency in technology and livelihood education modules if students across year levels - Cunan, Florabelle R.; Banta, Evangeline S. (2014)
This paper is a program assessment of the different TLE modules offered for school year 2010-2011. For the past school years. TLE modules were all decided by the teachers. Students' opinions and suggestions were not taken into consideration. This study aims to see how the students rated the importance of the TLE modules and to determine students' self-perceived level of efficiency for in these modules. Other TLE modules were also included for the students to choose from to address their deficiencies. The results of this study helped in the formulation of the TLE modules for the succeeding school years.
Keywords: Modules (Technology and Livelihood Education)